Landasan Teknologis sebagai Peningkatan Mutu dalam Pendidikan dan Pembelajaran: Kajian Pustaka - Pinton Setya Mustafa; Muhammad Suryadi (FONDATIA, 2022)
The world of education and learning is developing in line with technological advances dynamically. In overcoming various increasingly complex problems in the world of education and learning, of course, new innovations are needed in providing the right solutions, one of which is developing education and learning patterns in accordance with the technological foundation. The purpose of this article is to provide study material on the technological foundations of education and learning. The method used in this qualitative research is a literature study, where information collection is carried out with documentation through books, journals, articles, and relevant juridical foundations. The technological foundation is the basis used as a reference for ethical theory and practice that involves people systematically supporting and solving various problems or improving quality in the education and learning process. The role of educational technology is basically an effort to improve the quality of education and learning from time to time and must be able to facilitate learning in various conditions encountered. The use of educational technology in general is to make it easier for students to access learning resources that are not limited by distance and time, so that learning can run effectively and efficiently and the quality of education will be better in the future. Conclusions from the presentation of these materials include educational technology which has a broad meaning that emphasizes the education system, while learning technology focuses on implementing learning that is in accordance with the conditions of students.